Media Diet Homogeneity in a Fragmented Media Landscape. Issue 1 (1st January 2017) - Young, Dannagal G.; Anderson, Katherine
ABSTRACT: This study assesses the nature of selective exposure and avoidance behaviors among political liberals and conservatives using a survey of 351 American citizens obtained through Amazon's Mechanical Turk. Analyses of a new "homogeneity of media diet" measure suggest that although liberals and conservatives consume a comparable total number of media sources, the homogeneity of those media sources is higher among liberals than it is among conservatives. In the sample examined here, liberals were significantly more likely than conservatives to selectively attend to ideologically onsonant media sources and were significantly more likely than conservatives to selectively avoid ideologically discrepant media sources. Analyses include a validity test of the self-reported selective exposure used by Pew and others, as well as an examination of partisan perceptions of the ideological leanings of various media sources. Results indicate that conservatives are more likely than liberals to rate neutral media sources (e.g., CNN, USA Today, and network news broadcasts) as ideologically biased. Meanwhile, liberals are more likely than conservatives to perceive the bias in their ideologically consonant media sources. Implications for future studies of selective exposure and avoidance—and democratic theory in general—are discussed.